Pelaksanaan Tugas Dan Fungsi Badan Penanggulangan Bencana Daerah Dalam Penanggulangan Bencana Alam Menurut Peraturan Daerah Nomor 6 Tahun 2010 Di Kota Kupang Tentang Organisasi Dan Tata Kerja Bpbd Daerah Kota Kupang - Umbu Pati, Kevin Hosea Bani; Hage, Markus Y; Tupen, Rafael Rape (Law Faculty, Nusa Cendana University, 2023)
implementation of the duties and functions of the regional disaster management agency in dealing with natural disasters that occurred in kupang city, lack of personnel and inadequate disaster service facilities in dealing with disasters that occurred in kupang city. in this case, the regional disaster management agency is lacking in the number of personnel and facilities to deal with the disaster that occurred, the number of field personnel and facilities should be increased to be able to help the people affected by the disaster that occurred. the formulation of the problem in this research is (1) how is the implementation of the duties and functions of bpbd in dealing with natural disasters in the city of kupang in 2021? (2) what are the factors inhibiting the implementation of the duties and functions of the regional disaster management agency (bpbd) in managing natural disasters according to regional regulation number 6 of 2010 in the city of kupang. the method used in this research is empirical legal research, namely examining the implementation of the duties and functions of the regional disaster management agency according to regional regulation number 6 of 2010 concerning the organization and work procedures of the kupang city regional disaster management agency by looking at how this law is implemented in the community through results interviews and from observations. research location, kupang city regional disaster management agency office and kupang city community. the types of data used here consist of primary and secondary data. based on the research results, there are data and facts that the author has obtained, the author concludes that the kupang city regional disaster management agency is still lacking in the number of field personnel and the infrastructure is still inadequate. in connection with this case, the author draws the conclusion; (a) disaster management and handling of refugees is fast, precise, effective and efficient because there are many agencies and organizations that take part in disaster management, (b) the kupang city regional disaster management agency must add field personnel and infrastructure. suggestion: regional disaster management agency must increase special disaster training and education for officials at least once a month so that bpbd officials become reliable and skilled officials in dealing with disasters according to their respective topics.